PERFORMANCE EVALUATION: THE IMPACT OF THE FINANCIAL RATIOS ON PROFITABILITY PERFORMANCE OF NATURAL GAS DISTRIBUTION COMPANIES IN BANGLADESH - Huda, Md. Nazmul; Sabur, Md. Abdus (International Journal of Research -GRANTHAALAYAH, 2025)
Purpose: The study examines the relationship between financial ratios and their impact on the profitability of Bangladeshi natural gas distribution companies. Design/methodology: Five natural gas distribution companies are purposively selected and considering 10 years of data. Liquidity, efficiency, and solvency ratios are considered as independent variables, size and age as control variables and profitability regarded as dependent variable, Findings: The crucial financial ratio receivable collection period and GPM have significant negative impact and insignificant negative impact respectively on NPM, ROE, and ROA. The association between financial ratios and profitability ratios; efficiency ratios are positively related to net profit margin. Liquidity ratios, total assets turnover ratios and solvency ratios negatively affect net profit. The study also concludes that age and size have no significant impact on profitability. The findings suggest that companies must improve their financial ratios to sustain in the competitive business market. Management should collect accounts receivable from customers by improving customer relationships, creating an easy payment system, automating software, and providing incentives for advance payment, paid accounts payable for smooth gas supply, improving assets turnover by maintaining optimum assets, effective asset utilisation, inventory management, supply chain improvement, customer satisfaction, maintain transparency, employees motivation, and technology advancement.